2009
DOI: 10.1007/s10995-009-0447-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Stress on Low Birth Weight and Preterm Birth Outcomes Across Neighborhoods of South Carolina, 2000–2003

Abstract: Effects of maternal stress on LBW and PTB outcomes may be different for mothers living in different neighborhood contexts. Therefore, investigations that fail to examine places of residence would most likely not identify mothers at risk of LBW or PTB. Policies to improve birth outcomes need to target both places of residence and specific mediating or moderating factors associated with deprived neighborhoods of residence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(121 citation statements)
references
References 32 publications
5
110
1
5
Order By: Relevance
“…The release of CRH has been hypothesized to initiate the onset of labour [45] via a series biochemical processes while cortisol has been linked with IUGR [46]. This relationship is in line with observations of previous studies [32], [47]. Mothers living in a neighbourhood with a low coverage of safe water were observed to have LBW infants more often than those dwelling in a neighbourhood with a high coverage of safe water supply.…”
Section: Discussionsupporting
confidence: 84%
“…The release of CRH has been hypothesized to initiate the onset of labour [45] via a series biochemical processes while cortisol has been linked with IUGR [46]. This relationship is in line with observations of previous studies [32], [47]. Mothers living in a neighbourhood with a low coverage of safe water were observed to have LBW infants more often than those dwelling in a neighbourhood with a high coverage of safe water supply.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, the novel finding of an association between depression and raised sAA is particularly pertinent when considering foetal development and offspring outcomes, because increased vasoconstriction may have implications for reduced foetal blood flow, growth and development. Thus, increased SNS activity could potentially explain why a number of observational studies have reported associations between prenatal mood disturbance and low birth weight/preterm infants (Class et al, 2011;Copper et al, 1996;Nkansah-Amankra et al, 2010;Sable and Wilkinson, 2000;Zhu et al, 2010). However, it should be noted that direct studies of mood disturbance and uterine artery resistance have, in the main, failed to identify significant associations between mood disturbance and decreased foetal blood flow (Harville et al, 2008;Kent et al, 2002;Mendelson et al, 2011;Monk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, prenatally distressed women are at greater risk of both preterm birth (Class et al, 2011;Copper et al, 1996;Nkansah-Amankra et al, 2010) and of having a low birth weight baby (Sable and Wilkinson, 2000;Zhu et al, 2010), which increases risk for offspring diabetes (Whincup et al, 2008) and cardiovascular disease (Barker, 1999;Huxley et al, 2007) in later life. Further, exposure to maternal psychological distress has been linked with increased rates of behavioural and emotional problems in childhood (O'Connor et al, 2002b(O'Connor et al, , 2003 and increased rates of psychiatric disease in adulthood (Pearson et al, 2013;Van den Bergh and Marcoen, 2004; Van den Bergh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that neighborhood conditions operate through the mediating factor of coping risk behaviors. Nkansah-Amankra et al 15 acquired data on 8,064 South Carolina women, their neonates, and their neighborhoods. Individual-level stress was measured and neighborhood disadvantage was classified.…”
Section: Discussionmentioning
confidence: 99%
“…The four recently published papers [13][14][15][16] all examined cross-sectional data for a single year or a few years. Here, I have looked at patterns at several points in time and seen differences in both the geography of low-weight birth incidence and in the independent variables of significant influence.…”
Section: What the Regressions Showmentioning
confidence: 99%